PENGATURAN PENDUDUK PENDATANG (KRAMA TAMIU ) DI TINJAU DARI HUKUM ADAT BALI - Kantriani, Ni Ketut (Institut Hindu Dharma Negeri Denpasar, 2018)
The problems caused by the influx of migrant population (Krama Tamiu) is the presence of immigrants who often do not report to the Village Prajuru, Head of the Environment and lack understanding of the rights and duties of the residence. In Balinese customary law is generally regulated about Krama Tamiu which is contained in Awig-awig Desa Adat / Desa Pakraman. Immigrants (Krama Tamiu / Tamiu) entering other areas, must know and follow the rules, as there is a convention between rights and obligations to be obtained and implemented. The immigrant population (Krama Tamiu) will receive a guidance (pasayuban) in the form of security guarantees, relief from all kinds of dangers that may occur during the respective stay in the region. As compensation for the rights it receives, the migrant population (Krama Tamiu) is subject to certain obligations whose type and form varies according to Awig-awig Desa Adat.